2017
DOI: 10.3390/su9091615
|View full text |Cite
|
Sign up to set email alerts
|

Economic, Environmental, and Animal Welfare Performance on Livestock Farms: Conceptual Model and Application to Some Case Studies in Italy

Abstract: Abstract:The aim of this paper is to propose a multi-attribute hierarchical evaluation model for the evaluation of the aggregate sustainability of livestock farms integrating the economic, environmental, and social aspects. This approach uses an aggregation criterion based on the geometric mean to assess a farm's current level of sustainability. Sustainability was measured through the use of indicators including carbon footprint, farm income, and animal welfare. Secondly, based on the relationships between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In that study, a comparison between the different dairy farms showed that a high efficiency of food conversion by animals was more effective in terms of environmental impact and, above all, in the production of greenhouse gases and the use of non-renewable energy. Therefore, aspects such as animal welfare, for example in extensive livestock management (more space available, access to pasture, quantity and quality of fresh forage, air quality) (67,68), could indirectly affect the environmental impact by operating on animal efficiency. At the same time, fresh forage may lead to a greater food conversion index and food efficiency (69), providing a positive impact on greenhouse gas emissions and on the environmental influence of livestock farming (70).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…In that study, a comparison between the different dairy farms showed that a high efficiency of food conversion by animals was more effective in terms of environmental impact and, above all, in the production of greenhouse gases and the use of non-renewable energy. Therefore, aspects such as animal welfare, for example in extensive livestock management (more space available, access to pasture, quantity and quality of fresh forage, air quality) (67,68), could indirectly affect the environmental impact by operating on animal efficiency. At the same time, fresh forage may lead to a greater food conversion index and food efficiency (69), providing a positive impact on greenhouse gas emissions and on the environmental influence of livestock farming (70).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Welfare is a central inextricable component of sustainability in livestock systems. Not only is it of moral and ethical importance, but it is also intertwined with animal health, productivity, economics, and environmental impacts ( 1 3 ). Consequently, animal welfare can both complement and conflict with other aspects of sustainability ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy on a national level, the study of INEA (Trisorio 2008) analyzes the sustainability of Italian agriculture on three dimensions (economic, ecological, and social) identifying for each a set of indicators that are measured in six geographical areas: Northeast, north, west, central, south, islands. More recently, in central Italy a methodology was developed to assess the sustainability of Dairy farming with respect to animal welfare, greenhouse gas emissions and profitability (Galioto et al 2017). The different aspects of sustainability addressed in this study were then interconnected to assess the cost faced by local farmers to improve animal welfare and to reduce Greenhouse gases (GHG) emissions.…”
Section: Introductionmentioning
confidence: 99%